2018
DOI: 10.3390/inventions3030051
|View full text |Cite
|
Sign up to set email alerts
|

Direct Assessment of Alcohol Consumption in Mental State Using Brain Computer Interfaces and Grammatical Evolution

Abstract: Alcohol consumption affects the function of the brain and long-term excessive alcohol intake can lead to severe brain disorders. Wearable electroencephalogram (EEG) recording devices combined with Brain Computer Interface (BCI) software may serve as a tool for alcohol-related brain wave assessment. In this paper, a method for mental state assessment from alcohol-related EEG recordings is proposed. EEG recordings are acquired with the Emotiv EPOC+, after consumption of three separate doses of alcohol. Data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Additionally, a sub-band morphological operation method has also been used successfully to detect cerebral aneurysms [56] and convolutional neural networks have been employed for the classification of leukocytes categories and leukemia prediction [57]. Furthermore, wearable electroencephalogram (EEG) recorders and Brain Computer Interface software have been proposed to aid in the assessment of alcohol-related brain waves [58]. More specifically, calculated spectral and statistical properties were used for classification, and Grammatical Evolution was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a sub-band morphological operation method has also been used successfully to detect cerebral aneurysms [56] and convolutional neural networks have been employed for the classification of leukocytes categories and leukemia prediction [57]. Furthermore, wearable electroencephalogram (EEG) recorders and Brain Computer Interface software have been proposed to aid in the assessment of alcohol-related brain waves [58]. More specifically, calculated spectral and statistical properties were used for classification, and Grammatical Evolution was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Only performing feature analysis from a single aspect will cause the loss of effective information. Tzimourta et al extracted six time domain features and five spectral features for analysis and found that the classification results using two fusion features are more ideal and the best accuracy reached 85.5% [ 17 ]. Hu, J. et al extracted four characteristics of sample entropy, fuzzy entropy, approximate entropy, and power spectrum entropy, and fused together as an input to the gradient-enhanced decision tree to determine whether the driver was in a fatigue state.…”
Section: Introductionmentioning
confidence: 99%
“…EEG sensors are wearable [ 6 ] non-invasive, portable and mobile [ 7 ], with excellent temporal resolution, and acceptable spatial resolution [ 8 ]. This humble diagnosis device is been transformed into currently the best approach to detect, out-of-the lab in an ambulatory context, information from the Central Nervous System and to use that information to volitionally drive cars, steer drones, write emails, control wheelchairs or to assess alcohol consumption [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%